Silent Pain: Non-Suicidal Self-Injury (NSSI) Among Late Adolescents with Abuse and Neglect Histories - Muhammad Lucky Chandra; Tabah Aris Nurjaman (Universitas Negeri Semarang, 2025)
Non-Suicidal Self-Injury (NSSI) is a significant mental health concern among late adolescents with histories of child abuse and neglect (CAN). This qualitative study employed Interpretative Phenomenological Analysis (IPA) to explore the lived experiences and psychological meanings of NSSI among three female late adolescents aged 19–21 years in Yogyakarta, Indonesia, who experienced CAN during childhood. In-depth interviews revealed that NSSI functioned not only as a maladaptive emotion regulation strategy but also as a form of moral self punishment and cognitive regulation. Participants engaged in self-injury to manage overwhelming emotional distress, silence intrusive thoughts, and punish themselves for perceived personal failure or ingratitude. Episodes of NSSI were frequently accompanied by dissociative experiences, including emotional numbness and delayed perception of pain. These behaviors were closely linked to internalized abusive caregiving patterns and difficulties expressing anger within interpersonal relationships. The findings highlight the enduring psychological impact of childhood maltreatment and underscore the importance of trauma-informed interventions that address emotion regulation, moral self-evaluation, and dissociative coping processes among late adolescents.